A investigação-acção-colaborativa como estratégia de formação inicial de professores na promoção do ensino da escrita - Maria da Conceição Medeiros Carvalho de (Universidade do Minho, 2002)
This text presents an empirical study that was developed within the context of an initial teacher training program. The research aimed at understanding the impact of collaborative action-research on the promotion of the teaching of writing skills. This strategy was part of a supervision framework that was oriented towards the professional development of three student-teachers. The results support the effectiveness of the training strategy that was used.